MAPPING POVERTY HOT SPOTS IN PENINSULAR MALAYSIA USING SPATIAL AUTOCORRELATION ANALYSIS - Majid, M. Rafee; Jaffar, Abdul Razak; Che Man, Noordini; Vaziri, Mehrdad; Sulemana, Mohamed (PLANNING MALAYSIA, 2016)
In September 2000 The Millennium Summit adopted the UN Millennium Declaration, committing nations to a new global partnership to reduce extreme poverty with a deadline of 2015. Eight Millennium Development Goals were formulated of which the eradication of poverty given top priority. However, Malaysia's participation with the UN in dealing with poverty, precede this when it committed itself with the United Nations Decade for the Eradication of Poverty (1997-2006) programme, which was then reinforced when the Millennium Declaration was made in 2000. Nationally, poverty eradication as well as bridging the inequality gap among the major ethnic groups and states has been the main development goal in Malaysia's development agenda since independence. In this regards, the principle of “growth with equity has been the central theme in all Malaysia's development policies and efforts since independence. Although Malaysia has made significant achievements in reducing the incidence of aggregate poverty across the country from 8.9% in 1995 down to 1.7% in 2012, there still exist pockets of poverty in the rural areas, in certain states/regions and among ethnic groups, as well as in some urban areas. This shows that formulating planning and policy implementation to eradicate poverty now needs to be more spatially focused for the implementation to be more effective. Recognising the incidence of poverty through standard statistical data tables alone is no longer adequate in formulating planning and policy implementation. Through spatial autocorrelation analysis the pattern of distribution of poverty in space over a period of time can easily be visualised and hotspots of incidence of poverty identified. This paper attempts to show how this analysis can assist in focusing efforts to eradicate poverty in Malaysia.